IMPLEMENTASI PERMENDAGRI NOMOR 4 TAHUN 2010 TENTANG PEDOMAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN MLONGO, KABUPATEN JEPARA - Setyaningrum, Cindy Ariantika; Suwitri, Sri; Rengga, Aloysius (Journal of Public Policy and Management Review, 2013)
Provision of public services "clean" is something that is expected by the community, see the deteriorating public services. In order to create public services that will be minimal corruption and so on, the government passed a law that Permendagri No. 4 of 2010 on Guidelines for Integrated Administrative Services District (PATENT). The purpose of the policy is to improve the quality PATENT and service closer to the community. This study aims to determine how the implementation PATENT in District Mlonggo and determine the factors that support or hinder the implementation so as to know what needs to be repaired and maintained.This study uses a descriptive qualitative research method, to explain phenomena that affect the implementation Permendagri No. 4 of 2010 on Guidelines for Integrated Administrative Services District (PATENT) in District Mlonggo. The data was collected by means of structured interviews with informants and documentation obtained from actual documents relating to the object of research. Analysis of the data in this qualitative study with data reduction, data presentation, and verification. From the research, found the phenomena that may affect implementation in the District Mlonggo PATENT, namely communication, resources, ingkungan conditions, as well as the attitude / disposition. It can be concluded that the implementation in the district PATENT Mlonggo there are factors that impede implementation. This is because the transmission process is not optimal, resulting in a lack of understanding of program beneficiaries. In addition, human resources and financial resources to support the facility's sustainability of the program has not been available for optimum.